Analisis Persepsi Masyarakat Terhadap Komunitas Peduli Lubang Jalanan di Kota Malang - Faizal Kurniawan (Universitas Trunojoyo Madura, 2018)
Malang Raya with all the trimmings is a city with intense activity. As a result, the streets in most areas in Malang became commonly used. The volume density of vehicles per day resulted in a lot of potholes. However, the slow handling of city government and county government resulted in the holes in the road more and more common. Of course this led to frustration for road users. Many victims of accidents caused fall due pit road. Not the least of casualties caused by potholes is pushing a bunch of young for forming Social Community “Peduli Lubang”. The group is moved voluntarily. Social counciosness encouraging to form this community. In its action, they make a circular mark or ledges with pylox white against the hole in every street. The goal is sign that the road users see the white markings they have made. The sign is effective because Driver can seen from distance before the hole, finally the driver can reduce speed. A lot of appreciation given to this community. Remaining so many hole in streets, and the number of